Let us march on : a novel - Moon, Shara (William Morrow, an imprint of HarperCollinsPublishers, 2025)
"Devoted wife, White House maid, reluctant activist... A stirring novel inspired by the life of an unsung heroine, and real-life crusader, Lizzie McDuffie, who, as a maid in FDR's White House, spearheaded the Civil Rights movement of her time"--